Recurrent solid ameloblastoma of the maxillary sinus: A case report - Martins de Paiva Tadeu Leonardo; Gama de Paiva Rosa Patrícia; Guimarães Henriques João César; Dantas Batista Jonas; Bardi Matai Viníícius Caio; Rangel Rosa Rafaela (Serbian Medical Society - Dental Section, Belgrade, 2012)
Introduction. Ameloblastomas are clinically the most important type of odontogenic tumors. Solid or multicystic form most commonly affects mandible, it is highly aggressive and shows high rates of recurrence. The aim was to report aggressive behavior of a rare maxillary solid ameloblastoma, emphasizing the clinical, tomographic and histological aspects. Case Report. A young and asymptomatic patient, presenting a solid ameloblastoma initially located in the maxillary sinus with rapid spreading to the adjacent tissues, had early recurrence despite radical surgical approach. Conclusion. Multicystic or solid ameloblastoma has lower incidence in maxilla and extremely aggressive behavior, justifying careful follow-up of the patients.